MINAT PETANI DALAM BERUSAHATANI PADI ORGANIK DAN PENGEMBANGAN KELEMBAGAANNYA DI KECAMATAN SAMBIREJO KABUPATEN SRAGEN - winarni, ayu (Berkala Ilmiah AGRIDEVINA, 2019)
Organic farming in Sambirejo District experienced very rapid development. This is driven by the emergence of farmers’ awareness to undertake safe, environmentally friendly and profitable efforts. This study aims to: 1) Analyze the factors that support the interest of farmers in organic rice farming in Sambirejo District and 2) Identify the role of institutions in the development of organic rice farming in Sambirejo District. The location of the study was in Sambirejo sub-district with informants 62 peoples and key informants 14 peoples with qualitative descriptive analysis method with a Grounded Theory approach. The results showed that the level of education of farmers is high (80%), the number of young farmers (75%), high extension frequency (100%), unspoiled soil (100%), natural water (100%), high selling price (100%) and high profits (100%) support the interest of farmers in organic rice farming in Sambirejo District. Institutions have a large share in the development of organic rice farming in Sambirejo District. The District Agriculture Office assists infrastructure facilities, Agricultural extension agent as the tongue of the farmer, Marketing Institution Markets farming results, Farmers' groups to exchange ideas and information, The Livestock Service Office supports the availability of manure, Organic fertilizer companies help provide organic fertilizer and INOFICE (Indonesian Organic Farming Certification) as an organic food guarantee institution. DOI : https://doi.org/10.33005/adv.v8i1.1610